Moshe Bar Kepha's commentary on the gospel of Luke - Mušē Bar-Kēpā 813-903 (Gorgias Eastern Christianity studies, 2020)
"Moshe Bar Kepha was a prolific writer of the ninth century. His writings reflect various aspects of West Syriac theology and ecclesiology, and his literary legacy links the earlier Syriac exegetical tradition (beginning with Ephrem) with the Syriac 'Renaissance' of the eleventh to thirteenth centuries. His use of sources crosses Christian confessional boundaries in such a way that his works are tinged with aspects of Syriac exegesis from both East and West Syriac traditions. In his Commentary on Luke, the Muslim-dominated context in which Moshe lived is clearly evident in the background, and his aim is to fortify the credibility of the Christian faith and the validity of Christian doctrines for his readers"--